2015
DOI: 10.1137/12089538x
|View full text |Cite
|
Sign up to set email alerts
|

Phase coexistence and torpid mixing in the 3-coloring model on ${\mathbb Z}^d$

Abstract: We show that for all sufficiently large d, the uniform proper 3-coloring model (in physics called the 3-state antiferromagnetic Potts model at zero temperature) on Z d admits multiple maximal-entropy Gibbs measures. This is a consequence of the following combinatorial result: if a proper 3-coloring is chosen uniformly from a box in Z d , conditioned on color 0 being given to all the vertices on the boundary of the box which are at an odd distance from a fixed vertex v in the box, then the probability that v ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(61 citation statements)
references
References 37 publications
(100 reference statements)
1
60
0
Order By: Relevance
“…In this work, we prove the high-dimensional case of the Kotecký conjecture, showing that for sufficiently high d there exists a positive temperature below which the model exhibits six BSS phases. Our methods also improve the quantitative sublattice bias estimates obtained in [34] and [18] for the zero-temperature case. and Z τ Λ,β , the partition function of the model, is a normalizing constant.…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…In this work, we prove the high-dimensional case of the Kotecký conjecture, showing that for sufficiently high d there exists a positive temperature below which the model exhibits six BSS phases. Our methods also improve the quantitative sublattice bias estimates obtained in [34] and [18] for the zero-temperature case. and Z τ Λ,β , the partition function of the model, is a normalizing constant.…”
mentioning
confidence: 69%
“…Already in [29], Kotecký observed that the problem resists standard Peierls arguments, and suggested looking at correspondences with other models as a possible approach for tackling it. The existence of six BSS phases was recently verified in the zero-temperature case in high dimensions by Peled [34] and, independently, by Galvin, Kahn, Randall and Sorkin [18]. Both groups obtained their results through highly sophisticated contour methods.…”
mentioning
confidence: 89%
See 3 more Smart Citations